The influence of national culture on the compensation system in selected countries - Gašić, Dimitrije (Anali Ekonomskog fakulteta u Subotici, 2021)
The escalating pace of globalization affects the increased need of organizations to develop effective compensation programs. Business cannot be imagined without one of the key things and that is human resources. Creative and productive employees are of great importance for the success of any organization. For the satisfaction and loyalty of employees, the compensation system, which consists of basic pay, incentive pay, and benefits, is of key importance. The goal of the compensation system is to simultaneously ensure the main goals of employees and employers, i.e. the purchasing power and satisfaction of employees, as well as the business success of the company. In times of crisis, determining the amount of basic pay, selecting adequate incentives, and offering various benefits became especially important. The aim of this paper is to present the basic elements of the compensation system in twenty countries around the world and to analyze the impact of national culture on the compensation system. The paper will present the following dimensions of national culture according to Hofstede’s classification: distance from power, individualism versus collectivism, male versus female cultures, avoidance of uncertainty, long-term versus short-term orientation, compliant versus restrained cultures. The analysis included twenty countries around the world, which are grouped as follows: the first 8 countries are members of the EU, the other 6 countries are located in the CEE region and the last 6 countries represent very important countries around the world. The paper determines the influence of the dimensions of national culture on the compensation system in selected countries from the European Union, the region of Central and Eastern Europe, and other countries, the paper is the basis for further research in this area.